The Relationship between the Biofilm Genes and Antibiotic Resistance in Stenotrophomonas maltophilia - Sameni, Fatemeh; Hajikhani, Bahareh; Hashemi, Ali; Owlia, Parviz; Niakan, Mohammad; Dadashi, Masoud (International Journal of Microbiology, 2023)
Objectives. Today, Stenotrophomonas maltophilia (S. maltophilia) is a major opportunistic pathogen among hospitalized or immunocompromised patients. Antibiotic-resistant clinical isolates are increasing in several parts of the world. Various antibiotic-resistance and biofilm-forming genes are identified in this bacterium. Its capacity to form biofilms is an important virulence factor that may impact antibiotic-resistance patterns. In the current study, we evaluated the biofilm-formation capacity, antibiotic-resistance profile, and prevalence of biofilm-forming genes as well as antibiotic resistance genes among S. maltophilia isolates. Materials and Methods. In this cross-sectional study, 94 clinical S. maltophilia isolates were recovered from four tertiary-care hospitals in Iran between 2021 and 2022. The presence of the selected antibiotic-resistance genes and biofilm-forming genes was examined by polymerase chain reaction (PCR). The ability of biofilm formation was examined by microtiter plate assay. The Kirby–Bauer disc diffusion method was used to evaluate the trimethoprim-sulfamethoxazole (TMP-SMX), levofloxacin, and minocycline resistance. Results. S. maltophilia is mainly isolated from bloodstream infections. Notably, 98.93% of isolates were biofilm producers, of which 19.35%, 60.22%, and 20.43% produced strong, moderate, and weak biofilm, respectively. The frequency of biofilm genes was 100%, 97.88%, 96.80%, and 75.53% for spgM, rmlA, smf-1, and rpfF, respectively. Isolates with the genotype of smf-1+/rmlA+/spgM+/rpfF+ were mostly strong biofilm producers. Among the antibiotic-resistance genes, the Smqnr, L1, and sul1 had the highest prevalence (76.59%, 72.34%, and 64.89), respectively. Antimicrobial susceptibility evaluation showed 1.06%, 3.19%, and 6.3% resistance to minocycline, TMP-SMX, and levofloxacin. Conclusion. The results of the current study demonstrated that S. maltophilia isolates differ in biofilm-forming ability. Moreover, smf-1, rmlA, and spgM genes were presented in all strong biofilm producers. Although the overall resistance rate to the evaluated antibiotics was high, there was no statistically significant relation between antibiotic resistance and the type of biofilm.